Maintenance of response and predictive factors of 1‐year GalcanezumAb treatment in real‐life migraine patients in Italy: The multicenter prospective cohort GARLIT study. (26th September 2022) - Vernieri, Fabrizio; Brunelli, Nicoletta; Marcosano, Marilena; Aurilia, Cinzia; Egeo, Gabriella; Lovati, Carlo; Favoni, Valentina; Perrotta, Armando; Maestrini, Ilaria; Rao, Renata; d'Onofrio, Luigi; Finocchi, Cinzia; et al.
Abstract: Background and Purpose: To evaluate the 1‐year effectiveness and tolerability of galcanezumab in real life and the prognostic indicators of persistent response. Methods: High‐frequency episodic migraine (HFEM) and chronic migraine (CM) patients treated with galcanezumab who completed a 1‐year observation were enrolled. The primary outcomes assessed during the 12 months (V1–V12) were the change in monthly migraine days (MMDs) from baseline and the response rates ≥50% in MMDs (MMD ≥50% RR). The secondary outcomes were changes in pain intensity (numerical rating scale [NRS]) and in monthly acute medication intake (MAMI). Results: We enrolled 191 patients (77.5% CM). Twenty‐three patients (12%) dropped out, two for nonserious adverse events. At least 40% of patients took add‐on standard preventives from baseline to V12. At V12, MMDs were reduced by 6.0 days in HFEM and by 11.9 days in CM patients (both p  < 0.00001); NRS and MAMI were also decreased in both groups ( p  < 0.00001). One‐hundred eight (56.5%) patients presented MMD ≥50% RR for 9 cumulative months (interquartile range=8): we defined this value as the cutoff for a persistent response. Persistent responders were less likely to have a higher body mass index (BMI) ( p  = 0.007) but more frequently had a good response to triptans ( p  = 0.005) and MMD ≥50% RR at V1 ( p  < 0.0000001). Patients without a persistent response were on add‐on therapy for longer periods of time ( p  < 0.001). Conclusions: Galcanezumab was effective and well‐tolerated in the 1‐year term, with most patients presenting MMD ≥50% RR for at least 9 months. Triptan response, lower BMI, and MMD ≥50% RR in the first month emerged as predictive factors for a persistent response. Abstract : How long is the response to galcanezumab in real life? Findings: In this longitudinal cohort study, considering 1‐year treatment, the included 191 patients presented a 50% response rate (RR) to galcanezumab for a median of 9 cumulative months. Favorable predictive factors were monthly migraine days ≥50% RR in the first month of therapy, and effective treatment of attacks with triptans, whereas higher body mass index negatively influenced the response. Meaning: In real‐life, galcanezumab demonstrated a rapid and sustained response over 1 year.